Removal of blood amyloid-β with hemodialysis reduced brain amyloid-β, confirmed by brain imaging: a case report - Kitaguchi N (Dove Medical Press, 2018)
Nobuya Kitaguchi,1 Takashi Kato,2 Shinji Matsunaga,3 Kyoko Hirano,4 Kaori Iwata,2 Kazunori Kawaguchi,1 Kiyoshi Fujita,5 Hajime Takechi,3 Midori Hasegawa,4 Yukio Yuzawa,4 Kengo Ito21School of Health Sciences, Fujita Health University, Toyoake, Aichi, Japan; 2Department of Brain Science and Molecular Imaging, Research Institute, National Center for Geriatrics and Gerontology, Obu, Aichi, Japan; 3Department of Geriatrics and Cognitive Disorders, School of Medicine, Fujita Health University, Toyoake, Aichi, Japan; 4Department of Nephrology, School of Medicine, Fujita Health University, Toyoake, Aichi, Japan; 5Okehazama Hospital, Fujita Kokoro Center, Seisinkai, Toyoake, Aichi, JapanAbstract: The accumulation of amyloid-β protein (Aβ) in the brain signifies a major pathological change of Alzheimer’s disease (AD). Extracorporeal blood Aβ removal system (E-BARS) has been under development as a tool for enhancing the clearance of Aβ from the brain. Previously, we revealed that dialyzers remove blood Aβs effectively, evoking substantial Aβ influx into the blood during hemodialysis sessions as one form of blood Aβ removal by E-BARS, and that postmortem brains of hemodialysis patients exhibited lower Aβ accumulation. Here, we present a case report of a 77-year-old male patient with end-stage renal failure whose Aβ accumulation in the brain declined by initiating and continuing hemodialysis for 6 months. This report suggests that blood Aβ removal by E-BARS could be an effective therapeutic method for AD.Keywords: amyloid-β, Aβ, PiB/PET, blood purification, blood Aβ removal, Alzheimer’s disease, E-BARS, extracorporeal blood Aβ removal system